A guide to managing and maintaining your PC introductory - Andrews, Jean (Course Technology, 1998)
This text helps computer users gain skills required to support and repair their own PCs. It covers how a computer works, as well as how to maintain, troubleshoot, upgrade and repair a PC. The text includes all of the topics covered in the current A+ Certification Exam (until 7/98).